HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN RAWAT JALAN PADA POLI PENYAKIT DALAM DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2025: HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN RAWAT JALAN PADA POLI PENYAKIT DALAM DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2025 - Lina Febriani Tanjung; Rizqi Nanda Putri (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
Hospital service quality is an important aspect in determining the level of patient satisfaction, especially in outpatient installations that have direct and repeated interactions. This study aims to determine the relationship between service quality and outpatient satisfaction at the Internal Medicine Clinic of Sembiring Deli Tua General Hospital in 2025. This study used a quantitative approach with a descriptive analytical design and cross-sectional method. A sample of 87 respondents was taken using the Lemeshow formula. The research instrument was a questionnaire that measured five dimensions of service quality based on the SERVQUAL model, namely tangibles, reliability, responsiveness, assurance, and empathy. The results of univariate analysis showed that the majority of respondents rated the service as